The Influence of the Knock-out Additive on the Mechanical Properties of Cores Made in the Core Blowing Process - Bobrowski, Artur; Kowalski, Jakub (AGH University Press, 2025)
The article presents the results of research on the effect of an additive improving shakeout (perlite ore with a specified grain size) on the mechanical properties of cores produced by the blowing process. The study was conducted on cores (standard specimens for tensile strength testing) made from core sands with varying amounts of loosening additive, depending on the core box temperature and shooting time, at a constant operating pressure of the shooting machine. The temperature of the core box at which the cores achieved the best mechanical properties was identified, and the necessity of optimizing both the amount of perlite ore additive and the binder content in the core sand to ensure the required mechanical properties of the cores was demonstrated.
Journal of Casting & Materials Engineering
Keywords: foundry; core sand; blowing process; inorganic binder; knocking-out; perlite ore